Implementation of Backpropagation Method with MLPClassifier to Face Mask Detection Model - Wendy Hendra Wijaya; Raymond Sunardi Oetama; Fransiscus Ati Halim (Universitas Multimedia Nusantara, 2022)
Corona Virus Disease 2019 (COVID-19) is a virus that has spread widely and has become a global pandemic. The virus also can be spread through droplets made from coughs or sneezes. The Minister of Health of the Republic of Indonesia has issued a decision regarding this COVID-19 pandemic case, one of which is